Spatiotemporal Dynamics of Free-Living and Particle-Associated Vibrio Communities in the Northern Chinese Marginal Seas - Liang, Jinchang (Appl Environ Microbiol, 2019)
Vibrio species are associated with human health and play important roles in the carbon cycle. The interest in the Vibrio ecology in marine pelagic environments has increased in recent years, and the correlations between the Vibrio community structure and various environmental factors have been demonstrated. However, the identification of planktonic Vibrio species and their relationship with particulate matter are unclear. Here, we elucidated the spatiotemporal dynamics of Vibrio diversity and in relation to environmental factors in the northern Chinese marginal seas, which feature complex and ever-changing environmental conditions. Vibrio abundance derived from quantitative PCR analysis was higher in summer (∼1.4 × 10(6) copies liter(−1)) than in winter (∼1.9 × 10(5) copies liter(−1)). Interestingly, the average amount of free-living (on a 0.22-μm-pore-size filter membrane) Vibrio was higher (∼3.89 times) than that of particle-associated Vibrio (on a 3-μm-pore-size filter membrane), making it likely that the preferential lifestyle of the planktonic Vibrio community was free living. Shifts in Vibrio community composition identified by high-throughput amplicon sequencing of the Vibrio-specific 16S rRNA gene were observed at both spatial and temporal scales, which were mainly driven by temperature, dissolved oxygen, ammonium, salinity, nitrite, and phosphate. The most prominent operational taxonomic units in summer were closely related to Vibrio campbellii and Vibrio caribbeanicus and shifted to those affiliated with Vibrio atlanticus in winter. Our study demonstrated abundant and diverse Vibrio populations in the northern Chinese marginal seas, contributing to a better understanding of their potential ecological roles in these ecosystems. IMPORTANCE The dynamics of Vibrio communities have been shown in many marine habitats that are close to land, including estuary or harbor areas. Here, we investigated the spatiotemporal dynamics of Vibrio populations in the northern Chinese marginal seas, spanning a wide spatial scale. We showed that the abundances of the Vibrio population in the present study were higher than those in most previously studied areas and that Vibrio species are more likely to adopt a free-living lifestyle. Moreover, our results expanded upon previous results by showing a clear shift in the dominant Vibrio species from summer to winter, which was mainly attributable to the reduction in the abundance of dominant species in summer. Overall, this work contributes to the understanding of the ecology of the Vibrio communities in the marginal seas.